Temporal self‐appraisal in depression and anxiety: A comparison between a clinical and non‐clinical sample. (17th December 2019) - Mathews, Stephanie; Williams, Ben; Nedeljkovic, Maja
Abstract: Objective: Temporal self‐appraisal theory proposes people perceive themselves as improving over time as a means of self‐enhancement. The current longitudinal study examined patterns of temporal self‐appraisal in individuals meeting criteria for a depressive and/or an anxiety disorder compared with healthy controls. Method: Thirty‐four participants who met criteria for a depressive and/or anxiety disorder and 109 healthy controls were asked to appraise themselves as they currently were and how they expected to be in 4 weeks' time. Four weeks later, 20 participants who met criteria for a depressive and/or anxiety disorder and 62 healthy controls appraised themselves as they currently were and how they were 4 weeks ago (58 and 56% retention, respectively). Results: Similar to healthy controls, participants with a depressive and/or anxiety disorder perceived the self on an upward trajectory over time. This occurred in the absence of actual improvement, reflecting self‐enhancing motives. Participants with a depressive and/or anxiety disorder had lower overall self‐appraisals. Conclusions: This highlights the need for therapy to target self‐appraisals in anxiety and depression. Patterns of temporal self‐appraisal may have a protective function in depression and anxiety that could be maximised in treatment.